Gallbladder cholesterosis without lithiasis: in respect of 18 cases. - Lago, Fernando; Carriquiry, Guillermo; Praderi, José; di Donna, Bruno; Estefan, Alberto (Cirugía del Uruguay, 1984)
Authors make a retrospective study of 18 cases ol gallbladder cholesterosis, without gallstones. Stressed are the finding of selective hyposthenic dyspepsia and/or pain in all cases, a very frequent association with obstructive siphopathies and the positive results obtained by this surgical treatment.